Palliative Care to Improve Quality of Life Patient with Hepatocellular Carcinoma - Muhamad Syarifudin; Domingos Soares (Proceeding of International Conference on Science, Health, And Technology, 2022)
Palliative care was multidiciplinary care that focuses on quality of life in patient with chronic disease. This intervention can be as support to patient with hepatocellular carcinoma. This study aimed was knowing about palliative care to improve quality of life patient with hepatocellular carcinoma. 5 databases were used in this literature search, they were Scopus, Pubmed, Proquest, Science Direct, and SAGE with keyword “Palliative care”, “quality of life” and “hepatocellular carcinoma”. Data was limited in last 5 years (2014-2019) and just literature in English that we are conducted. There were 15 selected journals from 2493 journal articles found. Palliative care was important for patient with hepatocellular carcinoma because it gave holistic care to patient and support for patient to suffer from cancer disease. Palliative give advantage for patients, and make them live longer, more comfort and ready to face peacefull end of life.